Isha Yoga Practices and Participation in Samyama Program are Associated with Reduced HbA1C and Systemic Inflammation, Improved Lipid Profile, and Short-Term and Sustained Improvement in Mental Health: A Prospective Observational Study of Meditators - Sadhasivam, Senthilkumar; Alankar, Suresh; Maturi, Raj; Williams, Amy; Vishnubhotla, Ramana V.; Hariri, Sepideh; Mudigonda, Mayur; Pawale, Dhanashri; Dubbireddi, Sangeeth; Packiasabapathy, Senthil; Castelluccio, Peter; Ram, Chithra; et al. (Frontiers in Psychology, 2021)
Background: Meditation is gaining recognition as a tool to impact health and well-being. Samyama is an 8-day intensive residential meditation experience conducted by Isha Foundation requiring several months of extensive preparation and vegan diet. The health effects of Samyama have not been previously studied. The objective was to assess physical and emotional well-being before and after Samyama participation by evaluating psychological surveys and objective health biomarkers. Methods: This was an observational study of 632 adults before and after the Isha Samyama retreat. All participants were invited to complete surveys. Controls included household significant others. Surveys were completed at baseline (T1), just before Samyama (T2), immediately after Samyama (T3), and 3 months later (T4) to assess anxiety, depression, mindfulness, joy, vitality, and resilience through validated psychometric scales. Voluntary blood sampling for biomarker analysis was done to assess hemoglobin (Hb), HbA1c, lipid profile, and C-reactive protein (CRP). Primary outcomes were changes in psychometric scores, body weight, and blood biomarkers. Results: Depression and anxiety scores decreased from T1 to T3, with the effect most pronounced in participants with baseline depression or anxiety. Scores at T4 remained below baseline for those with pre-existing depression or anxiety. Vitality, resilience, joy, and mindfulness increased from T1 to T3 (sustained at T4). Body weight decreased by 3% from T1 to T3. Triglycerides (TG) were lower from T2 to T3. Participants had lower HbA1c and HDL at T2, and lower CRP at all timepoints compared with controls. Conclusions: Participation in the Isha Samyama program led to multiple benefits. The 2-month preparation reduced anxiety, and participants maintained lower anxiety levels at 3 months post-retreat. Physical health improved over the course of the program as evidenced by weight loss and improved HbA1C and lipid profile. Practices associated with the Samyama preparation phase and the retreat may serve as an effective way to improve physical and mental health. Future studies may examine their use as an alternative therapy in patients with depression and/or anxiety. Clinical Trial Registration:www.ClinicalTrials.gov, Identifier: 1801728792. Registered retrospectively on 4/17/2020.